Исследование функций преобразования и чувствительности радиоизмерительного преобразователя давления - Osadchuk, V. S.; Osadchuk, A. V.; Gavryluk, G. I.; Bilokon, N. L. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Based on a nonlinear equivalent circuit of the pressure transducer, whose operation is described using Kirchhoff’s equations, the transfer function and sensitivity equation were obtained. The maximum sensitivity of the radio measurement transducer (13.75 kHz/kgf/mm²) lies in the pressure range above 0.5 kgf/mm².